Pemekaran Desa Dulupi - Aan Tahir; Siti Nurul Mokoginta (Jambura History and Culture Journal, 2021)
This study aims to determine how the expansion occurred in Dulupi Village in 2001. This study uses a qualitative method, namely a quantitative method that emphasizes deductive hypotheses and has limitations in reaching the problems studied. With these limitations, it is necessary to have alternative methods that can answer questions that cannot be answered by quantitative research methods. For this reason, this study uses a qualitative method.